PENCEMARAN LOGAM BERAT JENIS KADMIUM (Cd) DI PERAIRAN DAN DAMPAK TERHADAP IKAN (REVIEW) - THOY BATUN CITRA RAHMADANI; DAMAI DINIARIWISAN (GANEC SWARA, 2023)
Heavy metals are one of the problems in aquatic environment, both fresh and marine waters, because it has negative impact on aquatic organism like a fish and even humans. One type of dangerous heavy metal is Cadmium (Cd). It can cause several diseases such as bone disease (osteoporosis) and reproductive problems in humans. Source of Cd in waters can come from nature like weathering of rocks or volcanoes, but currently human activity is the biggest contributor. The biggest human activity as contributor is from industrial sector (e.g plastics, metal plating and electronics). It uses Cd as a raw material and generally disposes Cd waste into waters which are fish habitats. Cd in waters can accumulate in fish body and damage the gills, kidneys and liver. In the end, this problem will affect humans who consume fish contaminated with Cd on a large scale.